Secretion of Listeriolysin by Brucella suis Inhibits Its Intramacrophagic Replication - Köhler, Stephan (American Society for Microbiology, 2001)
The introduction into Brucella suis 1330 of a plasmid allowing the heterologous expression of a hybrid cytolysin containing listeriolysin from Listeria monocytogenes, and its export via the Escherichia coli hemolysin secretion pathway, resulted in secretion of active listeriolysin monitored by erythrocyte lysis. In contrast to observations with the nonhemolytic control strain, the phagosomes of infected human monocytes containing the hemolytic B. suis were partially disrupted, and this strain failed to multiply in human macrophage-like cells. These results added strong evidence supporting the proposal that the phagosome of the macrophage was the predominant niche of brucellae in their mammalian hosts.